Salmonella enterica Serotype Arizonae Meningitis in a Neonate - Wubishet Lakew; Abayneh Girma; Elizabeth Triche (Case Reports in Pediatrics)
Typhoidal and nontyphoidal salmonella infections are common causes of gastroenteritis in the community. However, salmonella only rarely causes invasive infections like meningitis. We report a 13-day-old female neonate with signs and symptoms of meningitis whose cerebrospinal fluid (CSF) culture showed Salmonella enterica serotype Arizonae that was sensitive to ceftriaxone. She presented with fever and failure to feed for 2 days. Despite prompt treatment with ampicillin, gentamicin, and ceftriaxone, she developed communicating hydrocephalus, frequent seizures, and coma that progressed to death after 2 weeks of hospitalization. Salmonella enterica serotype Arizonae is a rare cause of human infection known to leading to meningitis symptoms similar to those caused by other salmonella species. This is the first report of it as a cause of meningitis in a child under one month of age. Therefore, it should be included in the differential diagnosis of Gram-negative bacillary meningitis in immunocompromised children, neonates, and those with contacts with reptiles.